Rescue from lethal acute radiation syndrome (ARS) with severe weight loss by secretome of intramuscularly injected human placental stromal cells. Issue 6 (18th October 2018) - Pinzur, Lena; Akyuez, Levent; Levdansky, Lilia; Blumenfeld, Michal; Volinsky, Evgenia; Aberman, Zami; Reinke, Petra; Ofir, Racheli; Volk, Hans‐Dieter; Gorodetsky, Raphael
Abstract: Background: Most current cell‐based regenerative therapies are based on the indirect induction of the affected tissues repair. Xenogeneic cell‐based treatment with expanded human placenta stromal cells, predominantly from fetal origin (PLX‐RAD cells), were shown to mitigate significantly acute radiation syndrome (ARS) following high dose irradiation in mice, with expedited regain of weight loss and haematopoietic function. The current mechanistic study explores the indirect effect of the secretome of PLX‐RAD cells in the rescue of the irradiated mice. Methods: The mitigation of the ARS was investigated following two intramuscularly (IM) injected 2 × 10 6 PLX‐RAD cells, 1 and 5 days following 7.7 Gy irradiation. The mice survival rate and their blood or bone marrow (BM) cell counts were followed up and correlated with multiplex immunoassay of a panel of related human proteins of PLX‐RAD derived secretome, as well as endogenous secretion of related mouse proteins. PLX‐RAD secretome was also tested in vitro for its effect on the induction of the migration of BM progenitors. Results: A 7.7 Gy whole body mice irradiation resulted in 25% survival by 21 days. Treatment with two IM injections of 2 × 10 6 PLX‐RAD cells on days 1 and 5 after irradiation mitigated highly significantly the subsequent lethal ARS, with survival rate increase to nearly 100% and fast regain of the initial weight loss (P < 0, 0001). This was associated with a significant faster haematopoiesis recovery from day 9 onwards (P < 0.01). Nine out of the 65 human proteins tested were highly significantly elevated in the mouse circulation, peaking on days 6–9 after irradiation, relative to negligible levels in non‐irradiated PLX‐RAD injected mice (P < 0.01). The highly elevated proteins included human G‐CSF, GRO, MCP‐1, IL‐6 and lL‐8, reaching >500 pg/mL, while MCP‐3, ENA, Eotaxin and fractalkine levels ranged between 60–160pg/mL. The detected radiation‐induced PLX‐RAD secretome correlated well with the timing of the fast haematopoiesis regeneration. The radiation‐induced PLX‐RAD secretome seemed to reinforce the delayed high levels secretion of related mouse endogenous cytokines, including GCSF, KC, MCP‐1 and IL‐6. Additional supportive in vitro studies also confirmed the ability of cultured PLX‐RAD secretome to induce accelerated migration of BM progenitors. Conclusions: A well‐regulated and orchestrated secretion of major pro‐regenerative BM supporting secretome in high dose irradiated mice, treated with xenogeneic IM injected PLX‐RAD cells, can explain the observed mitigation of ARS. This seemed to coincide with faster haematopoiesis regeneration, regain of severe weight loss and the increased survival rate. The ARS‐related stress signals activating the IM injected PLX‐RAD cells for the remote secretion of the relevant human proteins deserve further investigation.